Incidence of Hypotension, Bradycardia, and Post-operative Nausea and Vomiting with Spinal Anesthesia in Cesarean Section Patient - Karnina, Resiana; Rahmadani, Shelina; Faruk, Muhammad (Open Access Macedonian Journal of Medical Sciences, 2022)
Background. Cesarean section is performed through an open abdominal incision (laparotomy) and an incision through the uterus (hysterotomy). Generally, cesarean section is performed with regional anesthesia techniques, with spinal anesthesia being the primary choice. Complications that often occur after the administration of spinal anesthesia include hypotension, bradycardia, and postoperative nausea and vomiting. The aim of this study was thus to identify the incidence of hypotension, bradycardia, and postoperative nausea and vomiting caused by spinal anesthesia during cesarean section procedures. Methods. This was a cross-sectional study with a descriptive, quantitative design. Data were obtained from the medical records of patients undergoing cesarean section procedures. Univariate analysis was performed to analyze data using IBM SPSS software version 28. Results. Univariate results showed that of the 297 samples, the incidence of hypotension based on mean arterial pressure was 1.7%, the incidence of bradycardia was 0.7%, and the incidence of postoperative nausea and vomiting was 3%. Conclusions. There was a 1.7% incidence of hypotension in patients undergoing cesarean section after spinal anesthesia, with 98.3% not experiencing hypotension. The incidence of bradycardia was 0.7% in cesarean section patients after spinal anesthesia, with 99.3% not experiencing bradycardia. The incidence of postoperative nausea and vomiting was 3% in cesarean section patients after spinal anesthesia, with 97% not experiencing postoperative nausea and vomiting.